2007
DOI: 10.1007/s10608-007-9120-7
|View full text |Cite
|
Sign up to set email alerts
|

The Ruminative Response Style in Adolescents: An Examination of Its Specific Link to Symptoms of Depression

Abstract: This study further examined the relation between a ruminative response style and symptoms of depression in nonclinical adolescents aged 12-18 years (N = 231). Participants completed questionnaires that measure rumination, neuroticism, and symptoms of depression and anxiety. Results indicated that rumination was significantly linked to symptoms of depression, and that this link remained significant when controlling for neuroticism. However, when concurrent anxiety symptoms were also taken into account, ruminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 49 publications
(58 reference statements)
5
35
1
1
Order By: Relevance
“…Los hallazgos del presente estudio verificaron así la validez convergente del BDI-IA con la CBAS, la ERR y el BAI, en congruencia con lo que se esperaba teóricamente, pues investigaciones previas señalan como componentes de la depresión a la rumia (Cova et al, 2009;Muris, FokkeBdi, validez en adolescentes éstas coocurren (Cova et al, 2009;Beck & Perkins, 2001). Incluso se ha propuesto que ambas corren a lo largo de un mismo continuo que apoya la noción de dimensionalidad de la depresión, según la cual la norma es que ésta generalmente se acompaña de síntomas de ansiedad, inatención y problemas de conducta.…”
Section: Discussionunclassified
“…Los hallazgos del presente estudio verificaron así la validez convergente del BDI-IA con la CBAS, la ERR y el BAI, en congruencia con lo que se esperaba teóricamente, pues investigaciones previas señalan como componentes de la depresión a la rumia (Cova et al, 2009;Muris, FokkeBdi, validez en adolescentes éstas coocurren (Cova et al, 2009;Beck & Perkins, 2001). Incluso se ha propuesto que ambas corren a lo largo de un mismo continuo que apoya la noción de dimensionalidad de la depresión, según la cual la norma es que ésta generalmente se acompaña de síntomas de ansiedad, inatención y problemas de conducta.…”
Section: Discussionunclassified
“…Previous research investigating the relationship between rumination and depression has primarily conceptualized rumination as having a main effect on depression (Broderick 1998;Broderick and Korteland 2004;Muris et al 2009;Nolen-Hoeksema and Girgus 1994). More recently, however, researchers have begun to consider additional mechanisms by which rumination may contribute to increases in depressive symptoms in adolescence.…”
Section: Rumination As a Moderator Of The Relationship Between Stressmentioning
confidence: 99%
“…These findings were interpreted as support for the hypothesis that rumination is a vulnerability factor specific to depression and not anxiety. In contrast to Hankin’s findings, Muris and colleagues (Muris et al, 2009; Muris et al, 2004) found that rumination was significantly associated with anxious symptoms, controlling for depressive symptoms, but rumination was unrelated to depressive symptoms when controlling for anxious symptoms. They interpreted their results as support for rumination as an anxiety-specific vulnerability, but conclusions about the specificity of rumination are difficult to draw from these studies.…”
mentioning
confidence: 69%
“…Rumination, the tendency to perseverate about the symptoms, causes, and consequences of negative mood, is a cognitive vulnerability that has been the focus of considerable research and one that has been consistently linked to concurrent and future levels of children’s depressive symptoms and disorders (see Rood, Roelofs, Bogels, Nolen-Hoeksema, & Schouten, 2009 for review). Originally proposed as a way of explaining risk for depression and the emergence of sex differences in depression in adolescence (Nolen-Hoeksema & Girgus, 1994), a growing body of research shows that rumination is also associated with increased risk of anxiety (Muris, Fokke, & Kwik, 2009; Muris, Roelofs, Meesters, & Boomsma, 2004), leading some researchers to propose that rumination is a transdiagnostic variable for anxiety and depression, rather than a cognitive vulnerability specific to depression (Ehring & Watkins, 2008; Nolen-Hoeksema, Wisco, & Lyubomirsky, 2008). …”
mentioning
confidence: 99%